(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
This paper focuses on seed germination of six indigenous medicinal plants of Bangladesh, namely Adenanthera pavonina L., Helicteres isora L., Murraya paniculata (L.) Jack, Psoralea corylifolia L., Uraria lagopodioides (L.) Desv. and U. picta (Jacq.) Desv. ex DC. The minimum days taken to germinate seeds in Adenanthera pavonina L., Murraya paniculata (L.) Jack, Psoralea corylifolia L., Uraria lagopodioides (L.) Desv. and U. picta (Jacq.) Desv. ex DC. are 12, 36, 10, 39 and 14, respectively. Seeds were not germinated in Helicteres isora L. indicating that seeds are not suitable for propagation, however, propagation through stem cutting in this species revealed that plants flowers and set fruits in the same year and take only six to seven months. Epigeal type of seed germination was observed in all cases. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19270 Bangladesh J. Plant Taxon. 21(1): 71-76, 2014 (June)